When payments for environmental services will work for conservation - Wunder, Sven (Wiley, 2013)
Using the article by Muradian et al. () as entry point, I develop a broader framework for the conditions needed to allow PES to emerge and function. It is argued that PES are designed as instruments with clear goals, and will function without markets, economic valuation, or commoditized services. As a highly adaptive management tool, PES are particularly suited for achieving equitable and flexible conservation outcomes. However, PES do require a payment culture and good organization from service users, a trustful negotiation climate, and well‐defined land‐ or resource‐tenure regimes for providers. These demanding preconditions may explain why PES implementation, while promising in many cases, has only spread slowly in low‐income countries.